2014
DOI: 10.1177/070674371405901008
|View full text |Cite
|
Sign up to set email alerts
|

The 6-Month Prevalence of Posttraumatic Stress Syndrome (PTSS) among Older Adults: Validity and Reliability of the PTSS Scale

Abstract: Objective: To document the 6-month prevalence of posttraumatic stress syndrome (PTSS) in the older adult population and the validity of a PTSS Scale in an epidemiologic setting.Method: Data came from the Enquête sur la santé des aînés et l'utilisation des services de santé (ESA Services Study) conducted during 2012-2013 using a probability sample of older adults seeking medical services in primary health clinics. Results:Results showed that a first-order PTSS measurement model consisting of 3 indicators-the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…The point prevalence of substantial PTSD/clinically important PTSD symptoms based on questionnaire thresholds ranged from 2.9% to 39.1% (15 studies 17, 19, 21, 22, 26, 27, 33, 38, 40, 42, 46, 5329, 34, 36 ). The median point prevalence of PTSD in all primary care samples was 12.5% (civilian population median [N = 21]: 11.1%, special risk population median [N = 3]: 12.5%, and veteran median [N = 7]: 24.5%).…”
Section: Resultsmentioning
confidence: 99%
“…The point prevalence of substantial PTSD/clinically important PTSD symptoms based on questionnaire thresholds ranged from 2.9% to 39.1% (15 studies 17, 19, 21, 22, 26, 27, 33, 38, 40, 42, 46, 5329, 34, 36 ). The median point prevalence of PTSD in all primary care samples was 12.5% (civilian population median [N = 21]: 11.1%, special risk population median [N = 3]: 12.5%, and veteran median [N = 7]: 24.5%).…”
Section: Resultsmentioning
confidence: 99%
“…We matched on these characteristics given known differences in mental health outcomes by gender (women typically report higher levels of PTSD 32 ), exposure to the storm, 7,25,29,51 and socioeconomic status. 29,31,34 Matching participants on geographic location in addition to ratings of exposure helped to account for the different types of damage individuals may have experienced, aligning individuals inland that likely experienced wind or tree damage and aligning those on the coastline who likely experienced damage such as flooding. Preliminary work within the larger study sample demonstrated that higher ratings of subjective exposure were linked with greater occurrence of PTSD after accounting for demographic and baseline clinical characteristics of participants (B = 0.35, SE = 0.01, P < 0.001, n = 2205).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding pre-disaster characteristics, PTSD has been consistently linked to gender (eg, women), 4,26,27,29,[31][32][33] lower income, 29,31,34 and marital status. 31,34 PTSD has also been linked to disability, 35 chronic health conditions, 36 prior trauma, [3][4][5][6] mental health comorbidities (eg, depression), 19,37,38 and health behaviors (eg, alcohol use). 39 Among peri-disaster variables, level of exposure has been confirmed as a perquisite to the development of PTSD.…”
Section: Factors Associated With the Development Of Ptsd In Older Adumentioning
confidence: 99%
“…The health and social services’ agency taking part in our study is responsible for a population of 1,325,000 inhabitants. The study population, data collection procedures and recruitment strategies are described in more detail in previous publications [ 17 , 18 ]. The study was approved by the ethics committee of the University of Sherbrooke’s Institute of Geriatrics.…”
Section: Methodsmentioning
confidence: 99%